Spatial Heterogeneity of Cx43 is an Arrhythmogenic Substrate of Polymorphic Ventricular Tachycardias during Compensated Cardiac Hypertrophy in Rats - Boulaksil, Mohamed; Bierhuizen, Marti F. A.; Engelen, Markus A.; Stein, Mèra; Kok, Bart J. M.; van Amersfoorth, Shirley C. M.; Vos, Marc A.; van Rijen, Harold V. M.; de Bakker, Jacques M. T.; van Veen, Toon A. B. (Frontiers in Cardiovascular Medicine, 2016)
Background Ventricular remodeling increases the propensity of ventricular tachyarrhythmias and sudden death in patients. We studied the mechanism underlying these fatal arrhythmias, electrical and structural cardiac remodeling, as well as arrhythmogeneity during early, compensated hypertrophy in a rat model of chronic pressure overload. Methods Twenty-six Wistar rats were subjected to transverse aortic constriction (TAC) (n = 13) or sham operation (n = 13). Four weeks postoperative, echo- and electrocardiography was performed. Epicardial (208 or 455 sites) and transmural (30 sites) ventricular activation mapping was performed on Langendorff perfused hearts. Subsequently, hearts were processed for (immuno)histological and molecular analyses. Results TAC rats showed significant hypertrophy with preserved left ventricular (LV) function. Epicardial conduction velocity (CV) was similar, but more dispersed in TAC. Transmural CV was slowed in TAC (37.6 ± 2.9 cm s−1) compared to sham (58.5 ± 3.9 cm s−1; P < 0.01). Sustained polymorphic ventricular tachycardias were induced from LV in 8/13 TAC and in 0/13 sham rats. During VT, electrical activation patterns showed variable sites of earliest epicardial activation and altering sites of functional conduction block. Wandering epicardial reentrant activation was sporadically observed. Collagen deposition was significantly higher in TAC compared to sham, but not different between arrhythmogenic and non-arrhythmogenic TAC animals. Connexin43 (Cx43) expression was heterogeneous with a higher prevalence of non-phosphorylated Cx43 in arrhythmogenic TAC animals. Conclusion In TAC rats with compensated cardiac hypertrophy, dispersion of conduction correlated to arrhythmogenesis, an increased heterogeneity of Cx43, and a partial substitution with non-phosphorylated Cx43. These alterations may result in the increased vulnerability to polymorphic VTs.